Management of soil pH for good soil health and high crop productivity - Sharma, S. S.; Sharma, R. P.; Sharma, S. K. (Indian Farming, 2015)
Soil reaction (pH) is the master variable of soil which affects all other variables of soil health and determines the soil and cropproductivity. Therefore, there is need to understand to manage soil pH in a way that sustainable soil health and crop productivity could be achieved. Often referred to as the master variable of soil, pH controls a wide range of physical, chemical, and biological processes and properties that affect soil fertility and plant growth.